Five-year outcome in 18 010 patients from the German Aortic Valve Registry . (4th May 2021) - Beyersdorf, Friedhelm; Bauer, Timm; Freemantle, Nick; Walther, Thomas; Frerker, Christian; Herrmann, Eva; Bleiziffer, Sabine; Möllmann, Helge; Landwehr, Sandra; Ensminger, Stephan; Bekeredjian, Raffi; Cremer, Jochen; et al.
Abstract:  : OBJECTIVES: To determine the 5-year outcome in patients treated by isolated transcatheter aortic valve implantation (TAVI) or surgical aortic valve replacement (sAVR)—a prospective observational cohort study. METHODS: A total of 18 010 patients were included ( n  = 8942 TAVI and n  = 9068 sAVR) in the German Aortic Valve Registry (GARY) who were treated in 2011 and 2012 at 92 sites in central Germany. Eligible patients with TAVI and sAVR were matched using propensity scores in a nearest-neighbour approach. Patients with repeat procedures or unequivocal indication for one treatment option (e.g. frailty) were excluded ( n  = 4785 for TAVI and n  = 2 for sAVR). This led to 13 223 patients (4157 TAVI and 9066 sAVR) as an unmatched subcohort. The main outcome measure was the 5-year all-cause mortality. RESULTS: TAVI patients were significantly older (80.9 ± 6.1 vs 68.5 ± 11.1 years, P  < 0.001), had a higher Society of Thoracic Surgeons (STS) score (6.3 ± 4.9 vs 2.6 ± 3.0, P  < 0.001) and a higher 5-year all-cause mortality (49.8% vs 16.5%, P  < 0.0001). There was no major difference in in-hospital stroke, in-hospital myocardial infarction, or temporary and chronic dialysis. In the propensity score-matched group ( n  = 3640), there were 763 deaths (41.9%) among 1820 TAVI patients compared with 552 (30.3%) among 1820 treated with sAVR during the 5-year follow-up (hazard ratio 1.51, 95% confidence interval 1.35–1.68; P  < 0.0001). New pacemaker implantation was performed in 448 patients (24.6%) after TAVI and in 201 (11.0%) after sAVR ( P  < 0.0001). CONCLUSIONS: The 5-year follow-up data show that TAVI patients were significantly older and had a higher STS score than sAVR patients. After propensity score matching, TAVI with early-generation prosthesis was associated with significantly higher 5-year all-cause mortality than sAVR.